Menginterkoneksi Sains dan Agama dalam Pembelajaran IPA di Sekolah Dasar - Yuliana Susanti (Pendidikan Agama Islam STIT Palapa Nusantara, 2019)
The development of science is interwoven with ideology. Therefore, a fundamental problem that always arises: is Islam complementary with natural science in harmony, or is there an unresolved complication between the metaphysical system based on religion and the demands of reason with empirical research? For a thousand years philosophers and Islamic theologians have considered this problem, which constantly invites intense and disagreeable debate. The word science comes from the Latin